COUNSELING COMPETENCE AND AWARENESS OF COMMON MENTAL HEALTH ISSUES AMONG GUIDANCE COUNSELORS AND DESIGNATES IN THE FIRST CONGRESSIONAL DISTRICT OF CAPIZ - Celino, Irah Celino Faith Denosta; Siglos, Caressa Lynn Aman; Ciudadano, Emmylou Demeties (President University, 2024)
This study aimed to assess the level of counseling competence and the degree of awareness ofcommon mental health issues of 128 randomly selected guidance counselors and designatesin the first congressional district of Capiz for academic year 2023-2024. Foreign and localliterature related to counseling competence and awareness of common mental issues werereviewed in relation to their relevance and implications to the study. A validated andreliability-tested researcher-made questionnaire was used to gather the needed data fromrandomly selected respondents. Statistical tools used to analyze and interpret data werefrequency count, percentage, mean, t-test, f-test, Analysis of Variance, and Pearson-r. Thefindings of the study revealed that respondents report a “high” level of counselingcompetence, and degree of awareness of common mental health issues. There weresignificant differences in the level of counseling competence and degree of awareness ofcommon mental health issues when respondents were grouped according to the nature oftraining, and number of trainings/seminars attended. Lastly, there was a significantrelationship between counseling competence and awareness of common mental issues. Thesefindings may aid in identifying counseling competence and mental health awareness gaps fortargeted evidence-based professional development programs, for the career developmentinitiatives of guidance counselors and designates.